LncRNA PPM1A-AS Regulate Tumor Development Through Multiple Signal Pathways in T-Cell Acute Lymphoblastic Leukemia - Li, Guoli; Lei, Xinyue; Zhang, Yingchi; Liu, Zhe; Zhu, Kegan (Frontiers in Oncology, 2021)
ALL (Acute lymphoblastic leukemia) is the most common pediatric malignancy and T-ALL (T-cell acute lymphoblastic leukemia) comprises about 15% cases. Compared with B-ALL (B-cell acute lymphoblastic leukemia), the prognosis of T-ALL is poorer, the chemotherapy is easier to fail and the relapse rate is higher. Previous studies mainly focused in Notch1-related long non-coding RNAs (lncRNAs) in T-ALL. Here, we intend to investigate lncRNAs involved in T-ALL covering different subtypes. The lncRNA PPM1A-AS was screened out for its significant up-regulation in 10 T-ALL samples of different subtypes than healthy human thymus extracts. Besides, the PPM1A-AS expression levels in 3 T-ALL cell lines are markedly higher than that in CD45+ T cells of healthy human. We further demonstrate that PPM1A-AS can promote cell proliferation and inhibit cell apoptosis in vitro and can influence T-ALL growth in vivo. Finally, we verified that PPM1A-AS can regulate core proteins, Notch4, STAT3 and Akt, of 3 important signaling pathways related to T-ALL. These results confirm that lncRNA PPM1A-AS can act as an oncogene in T-ALL and maybe a potential clinical target of patients resistant to current chemotherapy or relapsed cases.